Wykorzystanie narzędzi uzupełniających analizę zdyskontowanych przepływów pieniężnych netto w ocenie projektów badawczo-rozwojowych - Mielcarz, Paweł (The Application of Support Methods in the NPV Methodology in the R&D Project Appraisal Process, 2005)
The paper presents the importance of R&D projects for value creation. Then it indicates R&D valuation problems in the context of practices of Polish companies. Furthermore the author carried out an analysis of supporting techniques for standard net present value method in order to define the consequences of using them to R&D valuation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 299-319